An introduction to comparative legal models of criminal justice - Roberson, Cliff (CRC Press, 2008)
Common law model : the courts -- Policing and corrections under the common -- Civil law model : the courts -- Policing and corrections under the civil law -- The Islamic law model : the courts -- Policing and corrections under the Islamic legal model -- The socialist law model : the courts -- Policing and corrections under the socialist law -- Mixed law models -- International courts -- International criminal justice agencies and associations